Challenges in Surgery in COVID-19 Pandemic: Bangladesh Perspective - Mohammad, Din (Journal of Shaheed Suhrawardy Medical College, 2022)
Abstract not available J Shaheed Suhrawardy Med Coll 2021; 13(1): 1-2